The Behavioral Finance Perspective on MSMEs: Impact of Digital Finance, Financial Literacy, and Financial Inclusion - Prameswary, Raeesah Shalsabila Anjani; Muslimin, Muslimin (Universitas Mercu Buana, 2025)
This study aims to analyze the influence of Digital Finance, Financial Literacy, and Financial Inclusion on the financial management behavior of MSME actors in Bandar Lampung City. The research method used is quantitative, with data collected through surveys using questionnaires as the research instrument. The population in this study includes all MSMEs in Bandar Lampung City, with a sample of 105 MSME actors who meet the criteria as recipients of People’s Business Credit (KUR) or members of savings and loan cooperatives, have been operating for at least one year, and reside in Bandar Lampung City. The sample was determined using Hair’s formula, with a sampling technique based on purposive sampling, which is part of Non-Probability Sampling. Data analysis was conducted using Partial Least Square (PLS).The results indicate that Digital Finance, Financial Literacy, and Financial Inclusion positively influence financial management behavior. Digital Finance enhances transaction efficiency and financial recording accuracy, Financial Literacy assists in budget management and investment planning, while Financial Inclusion expands access to formal financial services. The implications of this study emphasize the importance of financial education and broader access to digital financial services to enhance the sustainability of MSMEs.